2019
DOI: 10.1073/pnas.1907968116
|View full text |Cite
|
Sign up to set email alerts
|

CsBRC1 inhibits axillary bud outgrowth by directly repressing the auxin efflux carrier CsPIN3 in cucumber

Abstract: Shoot branching is an important agronomic trait that directly determines plant architecture and affects crop productivity. To promote crop yield and quality, axillary branches need to be manually removed during cucumber production for fresh market and thus are undesirable. Auxin is well known as the primary signal imposing for apical dominance and acts as a repressor for lateral bud outgrowth indirectly. The TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) family gene BRANCHED1 (BRC1) has been shown to be the central in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 59 publications
5
74
0
Order By: Relevance
“…Our study identified seven genes in petunia belonging to the members of CYC/TB1 subclade, namely PaTCP1a/b, PaTCP12a/b and PaTCP18a/b/c, which are corresponding to the CYC2, CYC3 and CYC1 group, respectively. The three petunia CYC1 group of genes (PaTCP18a/b/c) are all expressed predominantly in vegetative axillary buds ( Figure 5), which is consistent with the expression patterns of BRANCHED1-like genes in other species, such as AtBRC1 (AtTCP18) and AtBRC2 (AtTCP12) in Arabidopsis [6], PsBRC1 in pea [65], SlBRC1s in tomato [66] and CsBRC1 in cucumber [67], suggesting that PaTCP18a/b/c have a conserved role in regulating axillary bud outgrowth and shoot branching. This was supported by the recent study that identified PhTCP3 (corresponding to PaTCP18c in this study) acting downstream strigolactone (SL) signaling to regulate lateral branching in petunia [51].…”
Section: Expression Patterns and Potential Functions Of Patcp Genessupporting
confidence: 81%
“…Our study identified seven genes in petunia belonging to the members of CYC/TB1 subclade, namely PaTCP1a/b, PaTCP12a/b and PaTCP18a/b/c, which are corresponding to the CYC2, CYC3 and CYC1 group, respectively. The three petunia CYC1 group of genes (PaTCP18a/b/c) are all expressed predominantly in vegetative axillary buds ( Figure 5), which is consistent with the expression patterns of BRANCHED1-like genes in other species, such as AtBRC1 (AtTCP18) and AtBRC2 (AtTCP12) in Arabidopsis [6], PsBRC1 in pea [65], SlBRC1s in tomato [66] and CsBRC1 in cucumber [67], suggesting that PaTCP18a/b/c have a conserved role in regulating axillary bud outgrowth and shoot branching. This was supported by the recent study that identified PhTCP3 (corresponding to PaTCP18c in this study) acting downstream strigolactone (SL) signaling to regulate lateral branching in petunia [51].…”
Section: Expression Patterns and Potential Functions Of Patcp Genessupporting
confidence: 81%
“…Increasing evidence verifies that TCP proteins are involved in responses to plant hormones (Braun et al, 2012;Danisman et al, 2012;Dun et al, 2012;Feng et al, 2018;Gonzalez-Grandio et al, 2017;Hay, Barkoulas & Tsiantis, 2004;He et al, 2016;Liu et al, 2018a;Lopez et al, 2015;Nicolas & Cubas, 2016;Qin et al, 2005;Schommer et al, 2008;Shen et al, 2019;Wang et al, 2019a;Wang et al, 2013). In this study, most of B. juncea var.…”
Section: Discussionsupporting
confidence: 63%
“…These results suggested that the role of WOX8/9 in regulating shoot architecture is conserved in different species. Recent studies showed that auxin plays important roles in regulating fruit length and shoot branching 32,41 . Future studies will need to unravel whether WOX9 controls branch growth by regulating auxin synthesis or/and transport.…”
Section: Discussionmentioning
confidence: 99%
“…4G; 6H-K,O,P). Previous studies showed that BRANCHED 1 (BRC1) inhibits shoot branching, while BLIND (BLIND) positively regulates axillary meristem formation [31][32][33][34] . To further confirm the role of CsWOX9 in regulating axillary bud outgrowth, we detected the expression levels of AtBRC1 and AtBLIND in CsWOX9 transgenic plants.…”
Section: Identification and Phylogenetic Analysis Of Cswox Genes In Cmentioning
confidence: 99%